2012
DOI: 10.1038/hr.2012.103
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium sulfate therapy of preeclampsia: an old tool with new mechanism of action and prospect in management and prophylaxis

Abstract: A disturbed balance between angiogenic and antiangiogenic growth factors is a highly accepted mechanism in the pathogenesis of pregnancy-induced hypertension and proteinuria, which is clinically known as preeclampsia (PE). We investigated the effect of magnesium sulfate (MgSO 4 ) therapy on vascular endothelial growth factor (VEGF), placental growth factor (PlGF), nitric oxide (NO) metabolites, soluble fm-like tyrosine kinase-1 (sFlt-1) and endoglin levels in PE rats and the effect of this treatment on the fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…For American pregnant females, it may be useful to prevent PE by lowering the age of pregnancy, reducing multipara, reducing weight appropriately and controlling weight gain during pregnancy. Furthermore, psychological stress may be a risk factor for pregnant females ( 82 , 83 ), which may be related to educational background and work intensity (which may be reflected by their salary). The present results indicated that Chinese females have a similar educational level distribution to Americans.…”
Section: Individual Therapy For Pementioning
confidence: 99%
“…For American pregnant females, it may be useful to prevent PE by lowering the age of pregnancy, reducing multipara, reducing weight appropriately and controlling weight gain during pregnancy. Furthermore, psychological stress may be a risk factor for pregnant females ( 82 , 83 ), which may be related to educational background and work intensity (which may be reflected by their salary). The present results indicated that Chinese females have a similar educational level distribution to Americans.…”
Section: Individual Therapy For Pementioning
confidence: 99%
“…In eclamptic patients, according to the treatment protocol, we immediately started antioedematous therapy (solution Mannitol, dexamethasone). For the treatment and prevention of new eclamptic seizures, we used MgSO 4 , as it is the first choice medication, useful also as sedative and antihypertensive agent 7,14,16,17,[25][26][27][28][29][30][31][32] . Our main problem was BP regulation, complicated by the need for mechanical ventilation and, later, by fear, anxiety in awaken patient with tracheostomal cannula.…”
Section: Discussionmentioning
confidence: 99%
“…However, early pregnancy termination to alleviate PE increases both neonatal mortality and morbidity. Magnesium sulfate, which causes prostaglandin release and subsequent dilation of blood vessels, has been occasionally used as a therapeutic drug for PE [12,13,14]. Despite extending gestational age to some extent, magnesium sulfate does not reverse the development of PE but rather alleviates symptoms temporarily.…”
Section: Discussionmentioning
confidence: 99%